ҚАРАҚАЛПАҚСТАН РЕСПУБЛИКАСЫНДА ЭКОНОМИКАЛЫҚ РЕФОРМАЛАРДЫ ТЕРЕҢЛЕСТИРИЎ ҲӘМ ЭКОНОМИКАСЫНЫҢ ТУРАҚЛЫ РАЎАЖЛАНЫЎЫНЫҢ ТЕНДЕНЦИЯЛАРЫ - Сарыбаев, А.К. (SCIENCE and SOCIETY, 2023)
This article presents measures aimed at ensuring the stable development of all sectors of the national economy of the Republic of Karakalpakstan during the period of economic reforms that began in the country since the 2000s and in subsequent stages, as well as during the period of fundamental reforms of the economic sector in 2017-2021. Also, on the way to deepening economic reforms in the region, the issues of modernizing the economy are reflected, which shows the processes of increasing the private sector in the economy and social support for the population.
Keywords: modernization of the economy; reforms in industry; construction; agriculture and transport infrastructure; fundamental reforms of the economic sector; social protection; small business and private entrepreneurship; increasing the security of the population; "Iron Notebook"; "Women's Notebook" and "Youth Notebook"